2018
DOI: 10.1016/j.worlddev.2018.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Legalization, diplomacy, and development: Do investment treaties de-politicize investment disputes?

Abstract: Developing countries have entered into investment treaties for decades. One promise of signing up to these potent agreements was that it would allow risky investment climates to attract more capital. This proclaimed benefit of the investment treaty regime is subject to a large, and growing, empirical literaturewith mixed findings. Yet, another, and potentially far more important promise of the treaties has been entirely ignored in empirical literature. Architects of the investment treaty regime as well as many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Studies looking at the effects of IIAs have focused on the benefit side of the agreements, that is, their ability to attract investment (Bonnitcha, Poulsen, and Waibel 2017, 155-166) and to depoliticize disputes (Gertz, Jandhyala, and Poulsen 2018). Although enforceability through ISDS is the component of IIAs that make them credible commitments to foreign investors (Elkins, Guzman, and Simmons 2006), the legitimacy debate in the investment treaty regime seems to be driven by the realization that IIAs also carry "low-probability, high-impact risks" (Poulsen 2014, 2).…”
Section: Iv2 Iias and Isdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies looking at the effects of IIAs have focused on the benefit side of the agreements, that is, their ability to attract investment (Bonnitcha, Poulsen, and Waibel 2017, 155-166) and to depoliticize disputes (Gertz, Jandhyala, and Poulsen 2018). Although enforceability through ISDS is the component of IIAs that make them credible commitments to foreign investors (Elkins, Guzman, and Simmons 2006), the legitimacy debate in the investment treaty regime seems to be driven by the realization that IIAs also carry "low-probability, high-impact risks" (Poulsen 2014, 2).…”
Section: Iv2 Iias and Isdsmentioning
confidence: 99%
“…A broader question regarding selection in IIA-making that concerns the two latter biases discussed is what information states base their IIA-negotiation efforts on. While early empirical research worked on the assumption that states were rational actors with full information (Elkins, Guzman, and Simmons 2006), more recent empirical research, based on detailed archival and first hand data from negotiations, have shown that most states acted under bounded rationality when developing their IIA policies and negotiating IIAs (Bonnitcha, Poulsen, and Waibel 2017;Gertz, Jandhyala, and Poulsen 2018;Poulsen 2015). Importantly, it has shown that they frequently under-appreciated the risk of ISDS, and overappreciated the potential gains from IIAs (inwards investment; depolitization of investment disputes).…”
Section: Ivb2 Estimationmentioning
confidence: 99%
“…Finally, empirical scholarship has begun to assess the extent to which investment treaty arbitration may assist developing countries in 'depoliticizing' investment disputes -by removing the home state from the equation -but here again existing results have been disappointing. 77 The combination of significant political and economic costs associated with investment treaty arbitration and questionable economic and political benefits has made some developing countries rethink their support for the investment treaty regime. For example, while Latin American countries were particularly prolific in their adoption of BITs in the 1980s and 1990s, the tide has since turned, to the extent that Bolivia, Ecuador, and Venezuela have all ended some BIT agreements and withdrawn from the ICSID Convention.…”
Section: Economic Impactmentioning
confidence: 99%
“…Several studies have argued that there is an immense need for research on CD based on the escalated contemporized market integration practices, processes, and structures. Accordingly, past researches such as Georgiadou (2018) and Gertz et al (2018) have also highlighted that developing countries are unable to recognize the importance of CD.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%